Michigan Proficiency - Preliminary Practice Tests / For the Michigan Certificate of Proficiency in English Examinations - Flanel Piniaris Diane (New Editions, 1999)
This textbook contains 25 practice tests for the preliminary test of the University of Michigan Proficiency exam (ECPE). Preliminary Tests, Shades of Meaning (Shyness and Beauty and Mercy), At the Root of the Matter (Sen - Spec - Con), Subtle Differences (Spreading Out - Changing), The Long and the Short of It, Preposition and Phrasal Verb Round-up, Fearsome Foursomes, Good Things and Bad (Bene - Mal-), Ashes to Ashes - Dust to Dust, Time Out for Time, Preposition and Phrasal Verb Round-up, Impish and imp- Words, Liquid Language, Watery States and Stages, Quirky Quartets and Other Q-Words, Preposition and Phrasal Veb Round-up, The Pleasure Principle, Heredity: It Runs in the Family, Birds of a Feather and Other Animal Idioms, One Way or Another (Searching and Throwing), Preposition and Phrasal Verb Round-up, More Fearsome Foursome, Let There Be Light, Destructive Tendencies, A Planet is a Terrible Thing to Waste, Preposition and Phrasal Verb Round-up.